A book review on Vrkshaayurveda - Kumar , M P Sanal; Jigeesh, P P (International Research Journal of Ayurveda & Yoga, 2024)
One-Health, although a relatively recent term, gained global acceptance years ago. In India, as part of ecosystem preservation, they integrated various domains—animals, plants, and more—under the umbrella of One-Health. These living beings were revered and protected with utmost intensity. While safeguarding inanimate things is relatively straightforward, protecting living beings poses challenges due to diseases, often encountered on a daily basis. Consequently, developing a robust healthcare system for these domains becomes essential. This led to the evolution of Mrugayurveda and Vrkshayurveda. The Vedas were the earliest texts to mention treatments for animals and trees. On vrkshayurveda, Later works by authors like Salihotra and Surapala delve into comprehensive scripts on Vrkshayurveda. Among these, the renowned Upavana Vinoda, a chapter from Sarngadhara Padhadi by Sarngadharacharya (16 CE), focuses entirely on plant life. It covers everything from land examination for tree planting (bhoomi niroopana) to botanical marvels (vrkshayurveda parishishtam), including techniques to enhance plant product yields. Building upon this foundation, Vidvan K. Vasu Panikker published a Malayalam commentary on Vrkshayurveda in 1945–1946. In 2022, Kottakkal Arya Vaidya Sala’s publication division released the first edition of the same book as part of the P.K. Warrier Commemoration series, complete with English and Malayalam commentary, aiming to enhance global acceptance. The current edition spans 136 pages and is priced at Rs. 250